The Dialectics of Class struggle in Marqueze’s ‘One of These Days’ and The Biblical Parable ‘Ahab and Naboth’ - Neupane, Dipesh (Cognition, 2024)
This paper attempts to explore the class conflict and the struggle implicitly or explicitly inherent in “One of These Days” and “Ahab and Naboth” applying the conceptual frameworks of Conflict theory based on Marxism. Conflict theory views social and economic institutions as tools of the struggle between groups or classes, used to maintain inequality and the dominance of the ruling class. The dialectics of class struggle is inevitable in most of the societies. The ruling class or the oppressors exploit their subjects or even do not lag behind to take their life in order to serve or suit their interest and desires. The victimized cannot react immediately due to the fear engendered by the pomp of power and money of the higher class. Rather, they either face the terrible fate or become submissive unwillingly. When the interests and the desires of the higher or the ruling class center upon the exploitation and the oppression of the lower class for their happiness, there appears the conflict between them resulting into the class struggle. This paper explores how the ruling class having the feudal ideology oppresses and exploits the innocent people misusing their power. The paper seeks to answer the prominent question : why and how do the upper and the ruling class oppress and suppress the lower class or the common people? The pomp of power and money corrupts man as it instigates man to render atrocities towards common people. Being scared, the subordinate people cannot raise their voices and launch their protest for justice. Instead, they attempt to suppress their voices due to their apprehension.